The Acquisition, Transfer, and Depreciation of Knowledge in Service Organizations: Productivity in Franchises - Darr, Eric D.; Argote, Linda; Epple, Dennis (Management Science, 1995)
The paper examines the acquisition, depreciation and transfer of knowledge acquired through learning by doing in service organizations. The analysis is based on weekly data collected over a one and a half year period from 36 pizza stores located in Southwestern Pennsylvania. The 36 stores, which are franchised from the same corporation, are owned by 10 different franchisees. We find evidence of learning in these service organizations: as the organizations gain experience in production, the unit cost of production declines significantly. Knowledge acquired through learning by doing is found to depreciate rapidly in these organizations. Knowledge acquired through learning by doing is found to depreciate rapidly in these organizations. Knowledge is found to transfer across stores owned by the same franchisee but not across stores owned by different franchisees. Theoretical and practical implications of the work are discussed.